Leadership Development According to the Principles of Papanikadhamma of the Administers Wareesawat Sobdistrict Administrative Organization at Phanom Phrai District in Roi Et Province: Leadership Development According to the Principles of Papanikadhamma of the Administers Wareesawat Sobdistrict Administrative Organization at Phanom Phrai District in Roi Et Province - Srisom, Nanthaporn; Chantawaree, Sukanda; Phrakhrusutaworathammakit (RATANABUTH JOURNAL, 2026)
This research article aimed to study the level of leadership development of the administrators of Waree Sawat Subdistrict Administrative Organization, to compare public opinions toward the leadership development of the administrators as classified by personal factors, and to propose guidelines for leadership development based on the principles of Pāpaṇika Dhamma. The study employed a mixed methods research design consisting of both quantitative and qualitative approaches. In the quantitative phase, the sample group consisted of 360 participants residing within the administrative area of Waree Sawat Subdistrict Administrative Organization. Data were collected through questionnaires and analyzed using frequency, percentage, mean, standard deviation, t-test, and F-test. In the qualitative phase, in-depth interviews were conducted with 9 key informants, including monks and laypersons, and the collected data were analyzed through descriptive content analysis. The findings of the research indicated that the overall level of leadership development of the administrators of Waree Sawat Subdistrict Administrative Organization was at the highest level. Similarly, the overall level of leadership development based on the principles of Pāpaṇika Dhamma was also found to be at the highest level. Furthermore, the comparison of public opinions classified by personal factors revealed that differences in gender, age, educational level, occupation, and monthly income did not significantly affect opinions toward the leadership development of the administrators. Therefore, the research hypothesis was rejected. In addition, the study found that effective leadership development should incorporate all three principles of Pāpaṇika Dhamma, namely Cakkhumā (vision), Vidhūro (expertise and competence), and Nissayasampanno (human relations and social connectedness), in order to align with contemporary leadership development concepts and enhance organizational management efficiency as well as the effectiveness of public service administration